PENGARUH ISLAMIC GOVERNANCE, LEVERAGE, PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN DENGAN ISLAMIC SOCIAL REPORTING SEBAGAI VARIABEL MEDIASI : (Studi Kasus Pada Bank Umum Syariah Di Indonesia Yang Terdaftar Di Ojk Periode 2019-2023) - Alim, Saskia S; Muliati, Muliati; Parwati, Ni Made Suwitri; Kahar, Abdul (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: This study aims to analyze the effect of Islamic Governance, Leverage, Profitability, and Company Size on Company Value, with Islamic Social Reporting (ISR) as a mediating variable. The object of the study includes Islamic Commercial Banks registered with the Financial Services Authority (OJK) during the period 2019 to 2023. Methods: The research adopts a quantitative approach using the Partial Least Square (PLS) analysis method, processed through WarpPLS 8.0 software. The model is designed to test both direct and indirect effects between variables, particularly examining the mediating role of Islamic Social Reporting (ISR). Results: The results indicate that Islamic Governance and Islamic Social Reporting (ISR) have a direct positive and significant effect on company value. In contrast, leverage and profitability do not show a significant influence, while company size has a negative effect on company value. Furthermore, ISR does not significantly mediate the relationship between the independent variables (Islamic Governance, Leverage, Profitability, and Company Size) and company value. Conclusion and suggestion: The findings emphasize the importance of implementing Islamic Governance and Islamic Social Reporting to enhance the value of Islamic banks. While some financial indicators like leverage and profitability did not show significant influence, and company size negatively affected value, the role of sharia-based governance remains crucial. Future research is suggested to explore other potential mediators or extend the study to different sectors of Islamic finance to validate these findings. Keywords: Islamic Governance, Leverage, Profitability, Company Size, Islamic Social Reporting, Company Value.